Estudio de la diversidad arbórea de las comunidades indígenas San Luis de Armenia y Alto Mamduro ubicadas en la parroquia San Luis de Armenia del cantón Francisco de Orellana, provincia de Orellana y su influencia en la prestación de bienes y servicios ambientales - González Vega, Josías Daniel (2016)
The communities under study show loss of tree species caused by unplanned agricultural and livestock practices by the oil industry through the opening of several kilometers of access roads to extraction areas and the installation of oil pipelines facilitates the installation of settlers, Which has affected the expansion of the agricultural and livestock frontier. In order to gather information, a conglomerate composed of three "L" shaped parcels was installed at a distance of 250 m., Each parcels with a surface area of 3600 m² (60 m x 60 m). Trees with DAP ≥ 10 cm, recording for each individual (DAP), (HT) and (HC). The ecological parameters were calculated: absolute density, relative density, relative dominance, frequency and importance value index. For the environmental goods, the DBH ≥ 30 cm, plus the HC and for environmental services, were taken as variables only secondary forest ecosystems from a DBH ≥ 10 cm and HC. It was analyzed that the San Luis de Armenia community has a mean diversity (0.551) and the estimated total economic contributions by the main environmental goods and services is 94,924.5 usd / year and the Alto Mamduro community has a mean diversity (0.492 ) And the estimated total economic contributions for the main environmental goods and services is 424,712.4 usd / year. It can promote community projects jointly with governmental institutions and NGOs in the implementation of development activities that allow a sustainable and harmonic use of natural resources, seeking to ensure their permanence.